American experience. Stonewall uprising [videorecording (DVD)] - Davis, Kate, 1960 February 23-; Davis, Kate, 1960 February 23-; Heilbroner, David; Heilbroner, David; Carter, David, 1952- (PBS Distribution, 2011)
Explores the dramatic event that launched a worldwide rights movement. When police raided a Mafia-run gay bar in Greenwich Village, the Stonewall Inn on June 28, 1969, gay men and women did something they had not done before: they fought back. As the streets of New York erupted into violent protests and street demonstrations, the collective anger announced that the gay rights movement had arrived.